Clinical course and prognostic factors of Pneumocystis pneumonia with respiratory failure in non-HIV patients - Li, Jun; Mu, Xiangdong; Li, Haichao; Liu, Xinmin (Frontiers in Cellular and Infection Microbiology, 2024)
Background Compared with Human Immunodeficiency Virus (HIV) patients, non-HIV patients with Pneumocystis pneumonia (PCP) have more rapid onset, more rapid progression, and higher mortality. Objectives To investigate the predictive value of variables obtained upon hospital admission for in-hospital death and 90-day outcomes in non-HIV-PCP patients with respiratory failure (RF). Methods This was a single center retrospective study in a tertiary care institution over 15 years. It included all adults inpatients (≥18 years old) with laboratory confirmed non-HIV-PCP with RF who were discharged or died from Peking University First Hospital between April 1st, 2007 and November 1st, 2022. Epidemiological, clinical, laboratory, imaging and outcome data were collected from patient records. Results In this study, a total of 146 non-HIV-PCP patients with RF were included. There were 57 patients (39%) died during hospitalization, 44 patients (53%) died in Intensive care unit (ICU). A total of 137 patients completed 90 days of follow-up, of which 58 (42.3%) died. The multivariable regression analysis revealed that a CD8+ T cell count <115/μl (P=0.009), bronchoalveolar lavage fluid (BALF)-neutrophil percentage ≥50% (P=0.047), the time from corticosteroids withdrawal to symptom onset ≤5 days (P=0.012), and the time from visit to initiation of sulfonamides ≥2 days (P=0.011) were independent risk factors for in-hospital death. Furthermore, a CD8+ T cell count < 115/μl (P=0.001) and the time from visit to initiation of sulfonamides therapy ≥2 days (P=0.033) was independently associated with 90-day all-cause death. Conclusions A low CD8+ T cell count in peripheral blood, a high percentage of BALF-neutrophils, a short time from corticosteroids withdrawal to symptom onset, and a long time from visit to initiation of sulfonamides are associated with poor prognosis in non-HIV-PCP patients with RF.